ESG Disclosure and Sustainability Risk Governance in the Non-Financial Sector: Regulatory Perspectives and Policy Prioritisation - Galuh Tri Pambekti (Journal of Accounting Inquiry, 2026)
Purpose: This study examines whether Environmental, Social, and Governance (ESG) disclosure in Indonesia’s non-financial sector functions as an effective instrument for sustainability risk governance or remains largely a compliance-oriented reporting practice. Methodology: A qualitative policy research design is employed, integrating document analysis, policy-oriented Focus Group Discussions (FGDs) with senior officials from the Otoritas Jasa Keuangan, and the Analytic Hierarchy Process (AHP). Regulatory frameworks, corporate sustainability reports, and global ESG standards are analysed to assess the extent of risk integration, while FGD insights are prioritised using AHP to identify key policy interventions. Findings: Findings indicate a persistent gap between the growing volume of ESG disclosure and its limited functionality as a sustainability risk governance tool. Disclosures remain largely narrative, fragmented, and weakly embedded within enterprise risk management systems. Critical sustainability risks, including climate-related physical and transition risks, social conflicts, and governance failures, are insufficiently incorporated into supervisory assessments. AHP results identify the integration of ESG risks into risk-based supervision as the highest policy priority, followed by standardisation aligned with International Sustainability Standards Board (ISSB) and Task Force on Climate-Related Financial Disclosures (TCFD) frameworks, mandatory independent assurance, and capacity-building initiatives.  Novelty: A reconceptualisation of ESG disclosure is proposed, positioning it as a core instrument of risk governance within a risk-based supervisory architecture to strengthen early warning systems, mitigate greenwashing, and reinforce financial stability in emerging markets.